2018
DOI: 10.1111/jep.12988
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions, knowledge, and perceived barriers of Yemeni pharmacists and pharmacy technicians towards evidence‐based practice

Abstract: These results reveal strong support for EBP among pharmacists and pharmacy technicians in Yemen but only a minority indicated that they understood the technical terms of EBP. Training and continuing education programs on EBP and guidelines for pharmacists are strongly needed. These findings may help in planning the use and the application of EBP process in pharmacy practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…10 Unlike them, younger pharmacists had courses about evidence-based pharmacy and critical literature evaluation in their pharmacy degree programs, which would explain the differences. 11 Lack of formal education was just one of the recognized obstacles for research utilization. Pharmacists might not use the higher quality sources as they did not have time to perform the necessary literature search and analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Unlike them, younger pharmacists had courses about evidence-based pharmacy and critical literature evaluation in their pharmacy degree programs, which would explain the differences. 11 Lack of formal education was just one of the recognized obstacles for research utilization. Pharmacists might not use the higher quality sources as they did not have time to perform the necessary literature search and analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacists might not use the higher quality sources as they did not have time to perform the necessary literature search and analysis. 10,11 Senior pharmacists often had more responsibilities on managerial tasks which led to them having less time to work with the patients and utilizing evidence based pharmacy in their practice. 10 Furthermore, they might have only limited access to higher quality sources.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, those who had read such an article reported massive problems in understanding clinical trials. This could be explained by a lack of understanding basic evidence‐based terms revealed by other studies . Furthermore, other studies identified that free established databases for clinical studies such as MEDLINE or Cochrane Library are insufficiently known and underutilized …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have assessed the awareness, attitude, knowledge and skills of pharmacists towards evidence‐based practice . However, limited data are available on the current practical implementation of evidence‐based OTC counselling, particularly on the consideration of clinical trials for decision‐making …”
Section: What Is Known and Objectivesmentioning
confidence: 99%
“…Also, most of the resources they used to meet their information needs were non-evidence-based sources, and they preferred to consult their professors and colleagues. Al-Jamei et al (2019) reported that pharmacists had very little knowledge of the PubMed database and were unfamiliar with other databases. In Kalavani et al’s (2018) study, the use of specialized assistants with evidence-based medical databases was also reported as low.…”
Section: Discussionmentioning
confidence: 99%